Prospective evaluation of NGS-based sequencing in epilepsy patients: results of seven NASGE-associated diagnostic laboratories - Witzel, Maximilian G. W.; Gebhard, Christian; Wenzel, Sören; Kleier, Saskia; Eichhorn, Birgit; Lorenz, Peter; Heyden, Laura von der; Kuhn, Marius; Luedeke, Manuel; Döcker, Miriam; Jüngling, Jerome; Schulte, Björn; et al. (Frontiers in Neurology, 2023)
Epilepsy is one of the most common and disabling neurological disorders. The exact molecular diagnosis is essential to guide therapeutic decisions an counseling. Methods and materials: Here, we describe a prospective cohort study of patients with epilepsy evaluated in 7 NASGE-associated centers in Germany. Over a period of 2 months, 07/2022 through 08/2022, 304 patients (317 returned result) with seizure related Human Phenotype Ontology (HPO) were analyzed. Evaluated data included molecular results, phenotype and sequencing methods. Results: Single Exome Sequencing (SE) was applied in half of all patients, followed by panel (P) testing (36%) and Trio Exome Sequencing (TE) (14%). Overall, a pathogenic variant (PV) (ACMG cl. 4 /5) was identified in 22%; furthermore, a significant number of patients (12%) carried a reported clinically meaningful variant of unknown significance (VUS).The average diagnostic yield in patients ≤12y vs. >12y was higher in younger patients ((PV (PV+VUS): patients ≤12y: 23% (36%), patients >12y: 21% (32%)). This effect was more pronounced in cases, where TE was applied in patients ≤12y vs. >12y (PV (PV+VUS): patients ≤12y: 35% (47%), patients >12y: 20% (40%)). The highest diagnostic yield was achieved by TE in syndromic patients within the age group ≤12y (ACMG classes 4/5 40%). In addition, TE vs. SE had a tendency to result in less VUS in patients ≤12y (SE:19% (22/117) VUS; TE: 17% (6/36) VUS) but not in patients >12y (SE :19% (8/42)VUS; TE: 20% (2/10) VUS). Finally, diagnostic findings in patients with syndromic versus non-syndromic symptoms revealed a significant overlap of frequent causes of monogenic epilepsies, including SCN1A, CACNA1A, SETD1B, confirming the heterogeneity of the associated conditions. Conclusions: In patients with seizuresregardless of the detailed phenotype a monogenic cause can be frequently identified, often implying changes in therapeutic action (36.7% (37/109) of PV/VUS variants); this justifies early and broad application of genetic testing. Our data suggest that the diagnostic yield is highest in exome or trio-exome based testing, resulting in a molecular diagnosis within 3 weeks, with profound implications for therapeutic strategies and for counselling families and patients regarding prognosis and recurrence risk.